TEORI GRADASI:: KOMPARASI ANTARA IBN SĪNᾹ, SUHRAWARDĪ DAN MULLᾹ SHADRᾹ - Benny Susilo (Sekolah Tinggi Agama Islam Sadra, 2015)
Prior to Mullā Ṣadrā, the discussion of the gradation (al-tashkīk) was limited on the category of quality and that of quantity, both are known as the differential gradation (al-tashkīk al-tafāḍulī). In Ibn Sīnā’s point of view, the gradation occurs in the accidental matters (al-tashkīk fī al-‘araḍī) while in Suhrawardi’s, it occurs in the quiddity (al-tashkīk fī al-māhiyyah). Mullā Ṣadrā rejects both views and proves that essentially (bi al-dhāt) the gradation, in the specific sense, occurs in the reality of existence (tashkīk fī ḥaqīqat al-wujūd), while the gradation in the general sense just follows (bi al-ilḥaq) it. Using descriptive-analytical method and comparative approaches, this article is aimed to show the meeting points as well as separating ones of the thoughts of the three philosophers concerning gradation; also, to point out that Mullā Ṣadrā proceeds to elaborate two other kinds of gradation after proving the oneness in the reality of existence and asserting the differential gradation in it.